2019
DOI: 10.1097/corr.0000000000000903
|View full text |Cite
|
Sign up to set email alerts
|

Guided Growth Improves Coxa Valga and Hip Subluxation in Children with Cerebral Palsy

Abstract: Background Spastic hip subluxation or dislocation that is associated with an excessive coxa valga deformity is a common pathologic condition in children with cerebral palsy (CP) that is often treated with large bone reconstructive procedures. Guided growth techniques (such as stapling, plate, or transphyseal screw) have been widely used to alter the growth axis in patients with a lower-limb deformity but only a few reports have described their use in patients with coxa valga deformities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(67 citation statements)
references
References 38 publications
2
60
2
3
Order By: Relevance
“…While other studies have reported changes in MP between 10% and 15%, our case series showed a 5% change in MP over time. [11][12][13] Even with the lower magnitude of change, the change was shown to be statistically significant in our cohort. Our cohort of patients did have a smaller preoperative MP (27.3) in comparison to previous studies (preoperative MP in the range of 33.5 to 52.2) which could contribute to the smaller magnitude of change.…”
Section: Discussioncontrasting
confidence: 56%
“…While other studies have reported changes in MP between 10% and 15%, our case series showed a 5% change in MP over time. [11][12][13] Even with the lower magnitude of change, the change was shown to be statistically significant in our cohort. Our cohort of patients did have a smaller preoperative MP (27.3) in comparison to previous studies (preoperative MP in the range of 33.5 to 52.2) which could contribute to the smaller magnitude of change.…”
Section: Discussioncontrasting
confidence: 56%
“…In accordance with the above discussion, reversal of coxa valga by inferomedial screw epiphysiodesis of the proximal femoral physis has been investigated as a potential treatment of HD in CP. 34 Hsieh et al 35 reported significant decreases in HSA, MP, and AI in their cohort of children with CP HD, with longer follow-up duration and smaller preoperative MP associated with larger HSA reduction. The reduction in AI they identified at final follow-up supports the view that pressure from a laterally displaced femoral head is causative in the development of acetabular dysplasia.…”
Section: Discussionmentioning
confidence: 94%
“…In cases with dystonia, intrathecal baclofen application was shown to be beneficial [ 52 ]. Depending on the underlying problem, surgical procedures normally consist of derotational osteotomies [ 53 , 54 ], open reduction of hip dislocations with or without concomitant bony procedures [ 55 , 56 , 57 ], tenotomies [ 58 , 59 , 60 , 61 , 62 ] or guided growth with temporal (hemi) epiphysiodesis [ 63 , 64 , 65 , 66 ]. Care has to be taken with tenotomies for gaining more range of motion (ROM) of the affected joints which is generally accompanied by a further weakening of the muscle in our clinical experience.…”
Section: Preterm-related Orthopedic Disordersmentioning
confidence: 99%